FORUM: Give 'new kid on the block' a fair chance - Chang, Harry (Pacific Journalism Review : Te Koakoa, 1995)
Journalism lecturer Sorariba Nash's article, A free Ride to Propaganda, in PJR #1(1) is an example of blind, steel-trap tenacity. - Letters by Henry Chang (PNG), The National (Australia), Peter Cronau (Australia), David Ingram (Australia), and Suzanne Layton (Australia)
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjQxMzUvcGpyLnYyaTEuNTU0